Efficient redistribution: comparing basic income with unemployment benefits - Felix FitzRoy; Jim Jin (Institute for the Study of Labor (IZA), 2010)
We compare two systems of income redistribution: unemployment benefits (UB) and basic income (BI). First, for a simple utility function, with both intensive and extensive margins, the unemployed are likely better off with pure BI than pure UB, regardless of labour supply elasticity and wage distribution. Then we allow a general utility function and ignore intensive margins. For given unemployment, lowering UB and raising BI always benefits the unemployed, raises utilitarian welfare and benefits a poor majority. Reducing unemployment and UB simultaneously can benefit a majority of the employed as well as all unemployed, again for any wage distribution.
Keywords: H20; D40; 330; income distribution; basic income; unemployment benefits